The Impact of Triangle Hierarchical Management on Self-Management Behavior and Quality of Survival in Parkinson's Patients - Zeng, Yahua; Huang, Jianghua; Tang, Xuan; Wang, Ting; Chen, Shuangqin (Frontiers in Surgery, 2022)
Objective: To investigate the effect of Triangle tiered and graded management on the self-management behaviour and quality of survival of Parkinson's patients. Methods: 80 ambulatory Parkinson's patients admitted to the neurology outpatient clinic of our hospital from June 2020 to January 2021 were selected for the study. 80 patients were divided into 40 cases each in the experimental group and the control group using the random number table method. Patients in the control group were given conventional treatment and care, while in the experimental group, Triangle hierarchical management was applied on the basis of the control group. Non-motor symptoms [assessed by the Montreal Cognitive Inventory (MoCA), the Daytime Scale of Parkinson's Disability Scale (SCOPA-DS) and the Nocturnal Scale (SCOPA-NS)], motor symptoms [assessed by the Balance Gait Assessment Scale (FGA), the Modified Ashworth Scale, and the Parkinson's Disease Rating Scale Part III (UPDRS-III)], quality of life [assessed by the Morisky Medication Adherence Scale (MMAS-8)], and quality of life [assessed by the 39-item Parkinson's Disease Rating Scale (MMAS-8)] were compared between the two groups before and after the intervention. The two groups were also observed for satisfaction with care. Results:After the intervention, the MoCA score, FGA score, Barthel Index, MMAS-8 and all scores of self-management effectiveness were significantly higher in the experimental group than in the control group (P < 0.05); the SCOPA-DS score, SCOPA-NS score, Ashworth score, UPDRS-III score and PDQ-39 score were significantly lower than in the control group (P <0.05). Satisfaction with nursing care was significantly higher in the experimental group than in the control group (P < 0.05). Conclusion:The application of Triangle's tiered and graded management to the home care of ambulatory Parkinson's patients was effective in improving their non-motor and motor symptoms, their ability to perform daily activities, medication adherence and self-management effectiveness, and their overall survival outcome.